Dialogue about the pandemic and changes - Bagina, Elena; Grigoryeva, Elena (project baikal, 2022)
The coronavirus pandemic has claimed more than five million lives by early 2022. Changes have affected all people on the planet. New rules and laws have appeared, giving rise not only to discontent and social unrest, but also to new opportunities, which are mostly related to the digitalization of life, communication and “remote” work. The dialogue touches upon the necessity of changes in the life, housing typology and structure of the cities.
Keywords: pandemic; digitalization; changes in lifestyle; new types of housing; changes in the structure of large cities